2015
DOI: 10.1590/1983-1447.2015.esp.56723
|View full text |Cite
|
Sign up to set email alerts
|

Representações sociais das pessoas com tuberculose sobre o abandono do tratamento

Abstract: Educational strategies linked to social interaction processes, to subjectivity and to the patient context are needed to reduce the rates of discontinuation of tuberculosis treatment, relapses and multi-drug resistance. The evaluations point to new challenges that must be faced to achieve the Millennium Development Goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 9 publications
0
13
0
13
Order By: Relevance
“…Porém essa satisfação que se apresenta em algumas semanas de iniciado o tratamento, se deve ao fato de os sinais e sintomas começarem a desaparecer. O que pode tornar essa satisfação com a terapia em algo perigoso, já que alguns indivíduos se consideram "curados" e acabam abandonando o tratamento, fazendo com que se torne um paciente com um bacilo multirresistente (CHIRINOS et al, 2017).…”
Section: Resultsunclassified
“…Porém essa satisfação que se apresenta em algumas semanas de iniciado o tratamento, se deve ao fato de os sinais e sintomas começarem a desaparecer. O que pode tornar essa satisfação com a terapia em algo perigoso, já que alguns indivíduos se consideram "curados" e acabam abandonando o tratamento, fazendo com que se torne um paciente com um bacilo multirresistente (CHIRINOS et al, 2017).…”
Section: Resultsunclassified
“…This fact is concerning, because the nurse who works in a health institution should provide systematized care for the individual, family and community. In the context of TB control actions, one of their interventions is to guide these people regarding transmission and environmental measures to prevent the disease, in order to interrupt the disease transmission chain and demystify misconceptions about it, avoiding stigmas and treatment dropout (21) . Furthermore, as health professionals, their lack of knowledge can lead to the lack of individual safety measures, making them more vulnerable to contamination by the TB bacilli (16,(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…It may ease the burden on both the patient and family [43] [44] [45] [46]. Recent study showed that the presence of family or friends could be very decisive in matters relating to the maintenance of treatment, as it assists in the daily routines of basic health care and the compliance with the timetables of the medication [47] [48].…”
mentioning
confidence: 99%